Case report: Double adjacent ventral slot in two medium-sized breed dogs - Cojocaru, Razvan Grigore; Sicoe, Bogdan; Gaspar, Cristina; Grigoreanu, Alexandra; Orghici, Gabriel; Tibru, Ioan; Lacatus, Radu (Frontiers in Veterinary Science, 2024)
Two medium-sized, 7-year-old dogs with no previous history of pain, presented with acute neurologic symptoms consistent with intervertebral disc disease. Both cases had CT where cervical pathology was identified. In one dog the diagnosis was singular extensive cervical disc herniation with possible epidural hemorrhage and multiple-site cervical disc herniation in the other. The first dog, a Shar-Pei, underwent treatment with two standard adjacent ventral slots between the C4-C5 and C5-C6 intervertebral disc spaces, and a fenestration between the C3-C4 intervertebral disc space. The second case, a beagle, underwent a double adjacent standard ventral slot between C5-C6 and C6-C7 intervertebral disc spaces. Both dogs recovered uneventfully after the surgery and showed no signs of recurrence during a two-year follow-up period. This is the first detailed report of the use of a double adjacent ventral slot as a treatment for spinal decompression in medium-sized dogs with multiple-site spinal cord compression.